Relationship of visfatin with obesity and osteoporosis in patients with inflammatory bowel disease: a narrative review - Alicja Ewa Ratajczak-Pawłowska; Alicja Ewa Ratajczak-Pawłowska; Aleksandra Szymczak-Tomczak; Szymon Hryhorowicz; Agnieszka Zawada; Kinga Skoracka; Kinga Skoracka; Anna Maria Rychter; Anna Maria Rychter; Marzena Skrzypczak-Zielińska; Ryszard Słomski; Ryszard Słomski; et al. (Frontiers in Immunology)
BackgroundInflammatory bowel disease (IBD) is an increasingly prevalent condition in developed countries. Alongside the growing number of patients, there is a rising incidence of disease-related complications, including osteoporosis. While well-established risk factors for low bone mineral density in IBD—such as low body mass or steroid therapy—are widely recognized, other contributing factors warrant further investigation. One such factor is visfatin, a proinflammatory adipokine encoded by the NAMPT gene.ObjectivesThis review aimed to explore the association between visfatin level, bone health, and obesity among patients with inflammatory bowel disease.Key findingsAlthough visfatin is primarily associated with metabolic syndrome, it may also influence bone mineral density by affecting osteoblast and osteoclast differentiation and function. Additionally, some studies have identified a correlation between visfatin levels and bone mineral density. A deeper understanding of visfatin’s role in osteoporosis development may contribute to the identification of novel therapeutic strategies. Therefore, lower bone mineral density in inflammatory bowel disease may be associated with obesity and visfatin levels. However, visfatin concentrations depend on many factors, including genetics, immunology, and nutritional factors, which may affect visfatin levels.ImplicationsCurrent research highlights visfatin as both a potential biomarker and a therapeutic target for osteoporosis treatment. Nevertheless, limited studies have specifically examined the relationship between visfatin and bone mineral density in IBD. Further research is required to clarify this association and to explore how variations in visfatin levels impact bone density in IBD patients.